Anesthetic Cardioprotection: The Role of Adenosine - Bonney, Stephanie; Hughes, Kelly; Eckle, Tobias (Current Pharmaceutical Design, 2014)
Brief periods of cardiac ischemia and reperfusion exert a protective effect against subsequent longer ischemic periods, a phenomenon coined ischemic preconditioning. Similarly, repeated brief episodes of coronary occlusion and reperfusion at the onset of reperfusion, called post-conditioning, dramatically reduce infarct sizes. Interestingly, both effects can be achieved by the administration of any volatile anesthetic. In fact, cardio-protection by volatile anesthetics is an older phenomenon than ischemic pre- or post-conditioning. Although the mechanism through which anesthetics can mimic ischemic pre- or post-conditioning is still unknown, adenosine generation and signaling are the most redundant triggers in ischemic pre- or post-conditioning. In fact, adenosine signaling has been implicated in isoflurane-mediated cardioprotection. Adenosine acts via four receptors designated as A1, A2a, A2b, and A3. Cardioprotection has been associated with all subtypes, although the role of each remains controversial. Much of the controversy stems from the abundance of receptor agonists and antagonists that are, in fact, capable of interacting with multiple receptor subtypes. Recently, more specific receptor agonists and new genetic animal models have become available paving way towards new discoveries. As such, the adenosine A2b receptor was shown to be the only one of the adenosine receptors whose cardiac expression is induced by ischemia in both mice and humans and whose function is implicated in ischemic pre- or post-conditioning. In the current review, we will focus on adenosine signaling in the context of anesthetic cardioprotection and will highlight new discoveries, which could lead to new therapeutic concepts to treat myocardial ischemia using anesthetic preconditioning.
Keywords: heart ischemia